Differential expansion of the merozoite surface protein (msp)-7 gene family in Plasmodium species under a birth-and-death model of evolution (2010)
MSP-7 is a surface protein expressed by the Plasmodium merozoite as part of a protein-complex involved in initial interaction between merozoite and erythrocyte. Contigs of seven Plasmodium species were analyzed in order to identify all msp-7 family genes. The search identified annotated and unannotated open reading frames (ORFs) and showed an uneven number of msp-7 genes among the different species of the Plasmodium lineage. A phylogenetic analysis established the presence of at least two ancestral genes and identified various lineage- and species-specific duplication events. An estimation of synonymous (dS) and non-synonymous substitutions (dN) showed higher dS values compared to dN values, suggesting the action of purifying selection on these genes, moreover no changes in ? (evolutive rates) were found in codon models test. These data together with the data obtained from the Gu's type-I functional divergence test and comparisons between evolutionary rates among orthologous and paralogous genes suggest functional redundancy. Finally, an analysis of recombination events suggests that several sequences are undergoing such process and that this mechanism could therefore be playing an important role in the emergence of new sequences. We conclude that evolution of the msp-7 family is in agreement with a birth-and-death model of evolution, as msp-7 genes have expanded until reaching an optimal gene copy number in each Plasmodium species in order to adapt to different niches. © 2010 Elsevier Inc. All rights reserved.